A good and dignified life : the political advice of Hannah Arendt und Rosa Luxemburg - Hermsen, Joke J. 1961- (A Margellos world republic of letters book, 2022)
Rosa Luxemburg (1871–1919) and Hannah Arendt (1906–1975) were critical Jewish mavericks who both suﬀered under violent political regimes and sought to reform systems of power. Although temporally separated by the Second World War and the rise of totalitarianism, they held in common strikingly similar convictions about freedom, human dignity, capitalism, democracy, and political commitment. In this powerful book, Joke J. Hermsen explores the lives and works of these two remarkable thinkers and the essential hope that emboldened them in the political struggle. Luxemburg and Arendt were spurred on by a restless love for the world and an unwavering belief in the possibility of new beginnings; for them, hope was an absolute prerequisite of resistance and a counterpoint to melancholy—a defense against despair that kept them attuned to what could be. Exploring the intertwined nature of philosophy and the active pursuit of justice, this is an urgent, courageous reminder to remain alert to the glimmers of hope in dark times.